Factors influencing purchase intention toward residental property in Seri Alam by SSI Properties Sdn.Bhd / Nor Amira Mohd Jamal - Mohd Jamal, Nor Amira (Bachelor Of Business Administrations (HONS) Marketing, 2018)
Nowadays, property has becomes the most basic need for human life. Property is something that can ensure your life in future more better because the purchase of property never will make someone loss. As we notices, there are more developers in this challenging economy market conditions. They are very competitive to each other in order to sell their property by giving different kind of promotion, rebates and other than that. The purpose of this study was to determine the purchase intention towards a residential property in Seri Alam, Pasir Gudang. The main part of this study would be the factors of property view, property attribute and property surrounding. The data for this study was collected using a survey of questionnaire. Customers who walk into the sales gallery of Midas, Seri Alam would be the target population. A sample of 100 questionnaires was distributed to the respondent who have intention to purchase a residential property in Seri Alam, Pasir Gudang. The Statistical Package for Social Sciences (SPSS) version 22.0 was used to analyze the data collected through the survey. A few recommendations are presented to propose beneficial suggestions for future used.